A dual-metal center conductive nanomaterial glucose sensor and its preparation method and application
By covalently crosslinking the bimetallic center redox ligand with the conductive nanomaterial to form a new electronic mediator material, the problem of reduced sensitivity and weakened anti-interference ability caused by single metal center materials in the prior art is solved, and higher glucose sensor performance and longer working time are achieved.
Patent Information
- Application Number
- CN202210572540.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-05-24
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2042-05-24
AI Technical Summary
The use of single-metal center electronic media materials in existing second-generation CGMS wire enzyme technology leads to reduced sensitivity and weakened anti-interference ability.
Bimetallic center redox ligand is used to covalently cross-link with conductive nanomaterials to form a new electron mediator material, and the synergistic effect of bimetallic active centers is used to increase the electron transfer rate.
Improves the sensitivity and anti-interference ability of glucose sensors, extends effective working time, and reduces oxygen interference.
Smart Images

Figure HDA0003659649650000011 
Figure HDA0003659649650000012 
Figure HDA0003659649650000021
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of special materials and application technology for glucose intelligent monitoring, and specifically relates to a bimetallic central conductive nano glucose sensor and a preparation method thereof, and applications in glucose intelligent monitoring and diabetes management. Background Art
[0002] Currently, commercialized continuous glucose monitors (CGMS) all use electrochemical methods based on enzyme reactions to convert glucose concentration into electrical signals in real time. These CGMS products all contain glucose oxidase, which can specifically recognize glucose and is insensitive to other sugars in the body. The technologies used by the currently commercially available CGMS can be divided into first-generation enzyme technology and second-generation wired enzyme technology.
[0003] The first generation of enzyme technology indirectly detects glucose concentration by detecting the concentration of hydrogen peroxide produced during glucose oxidation, and the working electrode used is usually a precious metal electrode. The generation of hydrogen peroxide requires the consumption of oxygen, and the oxygen concentration in human blood (0.2-0.3 mM) is much lower than the glucose concentration in blood (5-10 mM), so it is necessary to cover the surface of the glucose sensor with a specially designed biocompatible outer membrane that can simultaneously control the flux of oxygen and glucose. This type of outer membrane material has a complex structure. For example, patent application documents such as patent application numbers CN201080053713.4, CN201080062485.7, and CN201980030243.0 disclose similar technologies. In addition, the diffusion direction of the generated hydrogen peroxide in the sensing layer is not restricted. Only hydrogen peroxide that diffuses to the electrode surface can generate current for sensing, so high requirements are placed on the preparation process of the electrode. In addition, the detection potential used in the first generation of enzyme technology is usually above 0.4V. At this potential, some interfering substances, such as ascorbic acid and acetaminophen, will be oxidized and generate interfering current. Therefore, the effective working time of CGMS based on the first generation of enzyme technology is usually 7 to 10 days.
[0004] The second generation of wired enzyme technology replaces oxygen with an artificially synthesized mediator to achieve electron transfer between glucose oxidase and the electrode. The electron mediator is grafted to the side chain of the polymer through a long flexible chain. The specific technical details are as shown in the US patent application document with publication number US6605200 B1. The redox center FAD of glucose oxidase is wrapped by a thick insulating layer. The mediator with a long flexible chain can achieve effective contact with FAD and transfer electrons. And through rapid reduction and rapid oxidation, carriers such as electrons or holes are formed, and current is conducted through self-exchange. The reduced mediator collides with the oxidized mediator, and the reduced mediator transfers electrons, or the oxidized mediator transfers holes. Although in theory, electrons or holes can also be transmitted by jumping between mediators in fixed positions, the trap-trap jump phenomenon of solid-state physics is rarely seen in redox hydrogels. The mediator with a long flexible chain transfers electrons faster than the mediator with a short chain. This is because the long flexible chain increases the displacement amplitude of the tethered mediator and significantly increases the contact collision frequency.
[0005] In addition, in the patent application document with patent application number CN200980139400.8, electronic mediators with different redox potentials are synthesized by adjusting the ligands of the synthetic mediators. The redox potentials of these electronic mediators are generally less than 0.3V, which improves the anti-interference ability of CGMS. Although the artificial synthetic mediator replaces oxygen to realize the electron transfer between glucose oxidase and the electrode, oxygen still transfers electrons with glucose oxidase. Therefore, there is a competitive relationship between oxygen and artificial synthetic mediators. Therefore, in documents such as CN113521399 A and US6932894 B2, a biocompatible outer membrane is prepared to reduce the penetration of oxygen into the sensing layer, while also controlling the flux of glucose to the sensing layer. Through this outer membrane, the interference of oxygen is reduced. However, oxygen, as a small molecule dissolved in body fluids, will still diffuse into the sensing layer along with water molecules in the slightly swollen pores, competing with the electronic mediator to transfer the electrons of glucose oxidase. If the cross-linking degree of the membrane is increased and the influx of oxygen is reduced, although the detection range of CGMS is further improved, the sensitivity will decrease and the detected current value will be more susceptible to external interference.
[0006] The CGMS electron mediators reported so far all use a single metal center, the most commonly used of which is based on metal osmium. They have slow electron transfer rates, weak anti-interference capabilities, and their sensing performance may be affected by oxygen concentration, and they have high requirements for the outer membrane. Summary of the invention
[0007] In view of the above-mentioned deficiencies in the prior art, the present invention provides a dual-metal center conductive nano glucose sensor and a preparation method and application thereof. The present invention can effectively solve the problems of reduced sensitivity and weakened anti-interference ability caused by the use of a single metal center in the existing electronic media material during the detection of glucose by the existing second-generation CGMS wired enzyme technology.
[0008] To achieve the above purpose, the technical solution adopted by the present invention to solve the technical problem is:
[0009] A dual-metal center conductive nano material glucose sensor comprises a conductive nano material connected with a dual-metal center redox ligand and a glucose oxidase covalently cross-linked with the conductive nano material.
[0010] Furthermore, the bimetallic redox ligand is connected to the conductive nanomaterial by covalent cross-linking, and the specific process is as follows:
[0011] The surface of the conductive nanomaterial is modified by using a silane coupling agent, and then the bimetallic center redox ligand is connected to the surface of the conductive nanomaterial by covalent cross-linking.
[0012] Furthermore, after the conductive nanomaterial and the silane coupling agent are mixed by ultrasound to obtain a uniform dispersion, 0.1M hydrochloric acid is added and then allowed to stand at room temperature for 6 to 48 hours to prepare the modified conductive nanomaterial.
[0013] Furthermore, the dosage ratio of the conductive nanomaterial to the silane coupling agent is 1:100 (in mg / mL).
[0014] Furthermore, the weight-to-volume ratio of the solution formed by the bimetallic redox ligand and the modified conductive nanomaterial is 0.1-10:1 (in mg / μL), wherein the concentration of the modified conductive nanomaterial solution is 200 mg / mL.
[0015] Furthermore, the bimetallic redox ligand includes Os(L)2RCl n and / or Rh(L)2RCl n ;
[0016] Wherein, L is a ligand containing two nitrogen heterocyclic rings, R is a monocyclic heterocyclic ligand or a bicyclic heterocyclic ligand containing a reactive group, and the value of n is 0 or 1.
[0017] Furthermore, when R is a monocyclic heterocyclic ligand containing a reactive group, n=1, and when R is a bicyclic heterocyclic ligand containing a reactive group, n=0.
[0018] Further, the bimetallic redox ligand comprises Os(L)2RCl in a weight ratio of 1:1 n and Rh(L)2RCln .
[0019] Furthermore, L is at least one of 2,2′-bipyridine and 4,4′-dimethyl-2,2′-bipyridine; and R is at least one of bipyridines having an amino group or a carboxyl group.
[0020] Furthermore, the general formula of the silane coupling agent is Y(CH2) n SiX3, wherein n is 0 to 3, X is a hydrolyzable group, and Y is a reactive functional group.
[0021] Furthermore, X is one or more of methoxy and ethoxy; and Y is one or more of amino and epoxy.
[0022] Furthermore, the conductive nanomaterial is carbon nanotube or graphene.
[0023] The preparation method of the bimetallic center conductive nanomaterial glucose sensor comprises mixing the conductive nanomaterial connected with the bimetallic center redox ligand, glucose oxidase and a crosslinking agent solution, and performing a crosslinking reaction at 20 to 45° C. for 45 minutes to 2 days.
[0024] Furthermore, the volume ratio of the conductive nanomaterial connected with the bimetallic center redox ligand, glucose oxidase and the crosslinker is 1:1:1; wherein the concentration of the conductive nanomaterial solution connected with the bimetallic center redox ligand is 10 mg / mL, the concentration of the glucose oxidase solution is 10 mg / mL, and the crosslinker accounts for 5% of its volume in the crosslinker solution.
[0025] Furthermore, the cross-linking agent includes but is not limited to glutaraldehyde, ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride and N-hydroxysuccinimide.
[0026] Application of the above-mentioned bimetallic center conductive nanomaterial glucose sensor in glucose monitoring and / or diabetes management.
[0027] Beneficial effects of the present invention:
[0028] 1. The present invention prepares a new type of electron mediator material through the redox ligand of the bimetallic active center, covalently connects it with the conductive nanomaterial, and utilizes the synergistic effect of the bimetallic active center to increase the rate of electron transfer of the electron mediator, thereby overcoming the oxygen effect in the second-generation wired enzyme technology; the electrochemical glucose sensor prepared using the sensing material provided by the present invention can specifically detect glucose, and its stable current signal has a high linear correlation coefficient with the glucose concentration, and can eliminate the influence of the interfering substance acetaminophen on glucose detection. Therefore, the conductive nano glucose sensing material based on redox ligand modification involved in the present invention has a wide range of application value in intelligent glucose detection.
[0029] 2. In the present invention, the redox ligand as an electron mediator realizes rapid electron transfer between bimetallic centers through covalent connection with the conductive nanomaterial, or the electron mediator directly transfers electrons to the next electron mediator through collision, or transfers electrons to multiple electron mediators connected to the surface of the conductive nanomaterial, or directly transfers electrons to the electrode through highly conductive nanomaterials to realize multi-path transfer. In this way, the rate of electron transfer by the electron mediator is greatly increased, effectively overcoming the oxygen effect.
[0030] 3. The conductive nano-material glucose sensor material provided by the present invention has a long effective working time due to its multi-path electron transfer and structural stability, and its working performance will not be affected by changes over time. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Figure 1 This is a cyclic voltammogram of the glucose sensing layer reagent in Example 1 of the present invention after being coated with a biocompatible layer in PBS;
[0032] Figure 2 This is a cyclic voltammogram of the glucose sensing layer reagent based on a single metal center in Example 1 of the present invention after being coated with a biocompatible layer in PBS;
[0033] Figure 3 This is the time current curve of the glucose sensing layer reagent in Example 1 of the present invention after being wrapped with a biocompatible layer in a 0-30 mM glucose PBS solution;
[0034] Figure 4 This is an anti-interference experiment after the glucose sensing layer reagent in Example 1 of the present invention is wrapped with a biocompatible layer;
[0035] Figure 5 This is a test experiment based on the glucose sensing layer reagent in Example 1 of the present invention wrapped with a biocompatible layer under different oxygen concentrations;
[0036] Figure 6 This is a long-term stability test of the glucose sensing layer reagent in Example 1 of the present invention after being coated with a biocompatible layer. DETAILED DESCRIPTION
[0037] The specific implementation modes of the present invention are described below so that those skilled in the art can understand the present invention. However, it should be clear that the present invention is not limited to the scope of the specific implementation modes. For those of ordinary skill in the art, as long as various changes are within the spirit and scope of the present invention as defined and determined by the attached claims, these changes are obvious, and all inventions and creations utilizing the concept of the present invention are protected.
[0038] Example 1
[0039] A conductive nanomaterial glucose sensor material based on redox ligand modification, the preparation process of which comprises the following steps:
[0040] A. Weigh 1 mg of multi-walled carbon nanotubes and place them in a 10 mL vial, add 1-3 mL of deionized water and 0.01 mL of 3-aminopropyltriethoxysilane, and ultrasonicate for 20 min to obtain a uniform dispersion, then place it at 25 ° C for 2 h, add 0.1 μL of 0.1 M hydrochloric acid, and place it at room temperature for 8 h. The obtained suspension is dialyzed, and the dialyzed suspension is washed by centrifugation for multiple times to obtain carbon nanotubes with amino groups on the surface;
[0041] B. 10 mg Os(bpy)2ClIm(CH2) 11 -COOH and 10 mg of Rh(bpy)2ClIm(CH2) 11 -COOH was fully dissolved in PBS at pH = 5 to 8 under stirring, and then 150 mg 1-ethyl-(3-dimethylaminopropyl) carbodiimide hydrochloride and 200 mg N-hydroxysuccinimide were added, and stirred at room temperature for 15 min. Then 100 μL of 200 mg / mL amino carbon nanotube dispersion (pH = 7.4) was added dropwise, and stirred at room temperature for 12 to 72 h. After the reaction was completed, the product was washed by centrifugation with deionized water, and then dialyzed with deionized water to remove free small molecules to obtain carbon nanotubes with surface modified redox ligands.
[0042] C. Mix 10 μL of the surface-modified redox ligand carbon nanotube dispersion (10 mg / mL) obtained in step B and 10 μL of glucose oxidase solution (10 mg / mL) with 10 μL of 5% glutaraldehyde solution for 45 min, and drop-coat the mixture onto the electrode surface to obtain a redox ligand-modified conductive nanomaterial glucose sensor reagent.
[0043] Example 2
[0044] A conductive nanomaterial glucose sensor material based on redox ligand modification, the preparation process of which comprises the following steps:
[0045] A. Weigh 100 mg of multi-walled carbon nanotubes and place them in a 10 mL vial, add 1-3 mL of deionized water and 1 mL of 3-aminopropyltriethoxysilane, and ultrasonicate for 20 min to obtain a uniform dispersion. Place it at 25 ° C for 4 h, add 100 μL of 0.1 M hydrochloric acid, and place it at room temperature for 6-48 h. The obtained suspension is dialyzed, and the dialyzed suspension is washed by centrifugation for multiple times to obtain carbon nanotubes with amino groups on the surface;
[0046] B. 100 mg Os(bpy)2ClIm(CH2) 11 -COOH and 100 mg of Rh(bpy)2ClIm(CH2) 11 -COOH was fully dissolved in PBS at pH = 5 to 8 under stirring, and then 150 mg 1-ethyl-(3-dimethylaminopropyl) carbodiimide hydrochloride and 200 mg N-hydroxysuccinimide were added, and stirred at room temperature for 15 to 60 min. 100 μL of 200 mg / mL amino carbon nanotube dispersion (pH = 7.4) was added dropwise, and stirred at room temperature for 12 to 72 h. After the reaction was completed, the product was washed by centrifugation with deionized water, and then dialyzed with deionized water to remove free small molecules to obtain carbon nanotubes with surface modified redox ligands.
[0047] C. Mix 10 μL of the surface-modified redox ligand carbon nanotube dispersion (10 mg / mL) obtained in step B and 10 μL of glucose oxidase solution (10 mg / mL) with 10 μL of 5% glutaraldehyde solution for 45 min, and drop-coat the mixture onto the electrode surface to obtain a glucose sensing layer reagent based on a conductive nanomaterial modified with redox ligands.
[0048] Example 3
[0049] A conductive nanomaterial glucose sensor material based on redox ligand modification, the preparation process of which comprises the following steps:
[0050] A. Weigh 40 mg of multi-walled carbon nanotubes into a 10 mL vial, add 1-3 mL of deionized water and 0.4 mL of 3-aminopropyltriethoxysilane, sonicate for 20 min to obtain a uniform dispersion, place at 25-50 ° C for 1-24 h, add 40 μL of 0.1 M hydrochloric acid, place at room temperature for 10 h, dialyze the obtained suspension, and wash the dialyzed suspension by centrifugation for multiple times to obtain carbon nanotubes with amino groups on the surface;
[0051] B. 40 mg Os(bpy)2ClIm(CH2) 11 -COOH and 40 mg of Rh(bpy)2ClIm(CH2) 11 -COOH was fully dissolved in PBS at pH = 5 to 8 under stirring, and then 150 mg 1-ethyl-(3-dimethylaminopropyl) carbodiimide hydrochloride and 200 mg N-hydroxysuccinimide were added, and stirred at room temperature for 20 min. 100 μL of 200 mg / mL amino carbon nanotube dispersion (pH = 7.4) was added dropwise, and stirred at room temperature for 30 h. After the reaction was completed, the product was washed by centrifugation with deionized water, and then dialyzed with deionized water to remove free small molecules to obtain carbon nanotubes with surface modified redox ligands.
[0052] C. Mix 10 μL of the surface-modified redox ligand carbon nanotube dispersion (10 mg / mL) obtained in step B and 10 μL of glucose oxidase solution (10 mg / mL) with 10 μL of 5% glutaraldehyde solution for 45 min, and drop-coat the mixture onto the electrode surface to obtain a glucose sensing layer reagent based on a conductive nanomaterial modified with redox ligands.
[0053] Experimental example
[0054] 1. Electrode cyclic voltammetry and anti-interference ability detection
[0055] The electrode obtained in Example 1 was used as the working electrode, silver / silver chloride was used as the reference electrode, and platinum wire was used as the auxiliary electrode. The cyclic voltammetry curve of the working electrode in a phosphate buffer solution of pH = 7.4 was tested. The results are shown in Figure 1 .
[0056] Depend on Figure 1 It can be seen that the redox peaks of these electrodes are below 0.1V, which is much lower than the voltage required for the catalytic oxidation of the interfering substance acetylamino and also lower than the voltage required for the catalytic oxidation of the interfering substance vitamin C. Therefore, these electrodes have good anti-interference ability.
[0057] For comparison, we also used single metal center electron mediators based on Os or Rh to make the same working electrode, and the oxidation front was around 0.3V ( Figure 2 ). Therefore, the anti-interference ability of the working electrode based on Os / Rh bimetallic center electron mediator is much better than that of the current single metal center electron mediator glucose sensor.
[0058] 2. Time-current characteristic detection
[0059] The time-current curve of the biocompatible layer coated with the glucose sensing layer reagent in Example 1 in a 0-30 mM glucose PBS solution, wherein the glucose concentration increases by 2 mM each time. Figure 3 As shown in the figure, as the glucose concentration increases, the current signal value also increases. And the glucose concentration and the current signal value have a good linear relationship. This result shows that the prepared electrodes can well test the glucose concentration in the range of 0-30mM glucose concentration.
[0060] 3. Anti-interference detection
[0061] The anti-interference experiment was carried out by wrapping a biocompatible layer with the glucose sensing layer reagent in Example 1. Figure 4As shown in the figure, the current signal values of these electrodes have a good linear relationship with the glucose concentration. After that, the PBS solution is replaced and 5mM acetaminophen is added, and the current value hardly changes. This result shows that the prepared electrodes have basically no response to acetaminophen, which shows that these electrodes have strong anti-interference ability to acetaminophen.
[0062] 4. Effect of oxygen concentration on electrodes
[0063] The glucose sensing layer reagent in Example 1 was used to wrap a biocompatible layer and then test the layer under different oxygen concentrations. Figure 5 As shown in the figure, in a 5% oxygen atmosphere, the current signal values of these electrodes show a relatively good linear relationship in the range of 0-50mM glucose concentration. Subsequently, nitrogen gas was blown into the test environment to change the oxygen concentration, and the current value hardly changed. This result shows that the prepared electrode is less affected by oxygen concentration.
[0064] 5. Stability test
[0065] The long-term stability test was conducted after the electrodes were coated with a biocompatible layer with the glucose sensing layer reagent in Example 1. After the electrodes were continuously operated in the test solution for 15 days, their sensitivity was tested every day. The results are as follows: Figure 6 As shown. The sensitivity on day 0 is the test result of the non-sterile electrode. The reason why the sensitivity on day 1 is lower than that on the subsequent 14 days is that the biocompatible layer has not completely swollen and balanced. The sensitivity of these electrodes changed little in the subsequent 14 days, which shows that the prepared electrodes have good stability and long-term stability of at least 14 days.
[0066] The above-mentioned embodiments only express the specific implementation methods of the present application, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the protection scope of the present application. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the technical solution concept of the present application, and these all belong to the protection scope of the present application.
Claims
1. A bimetallic center conductive nanomaterial glucose sensor, characterized in that: It includes a conductive nanomaterial connected with a bimetallic center redox ligand, and a glucose oxidase covalently cross-linked thereto; The step of connecting the bimetallic redox ligand and the conductive nanomaterial by covalent crosslinking comprises: modifying the surface of the conductive nanomaterial with a silane coupling agent, and then connecting the bimetallic redox ligand to the conductive nanomaterial by covalent crosslinking; The bimetallic redox ligand comprises Os(L)2RCl in a weight ratio of 1:1 n and Rh(L)2RCl n ; Wherein, L is a ligand containing two nitrogen heterocyclic rings, R is a monocyclic heterocyclic ligand or a bicyclic heterocyclic ligand containing a reactive group, and the value of n is 0 or 1; The weight-to-volume ratio of the bimetallic center redox ligand to the modified conductive nanomaterial is 2:1, expressed in mg / μL; The conductive nanomaterial is carbon nanotube or graphene.
2. The bimetallic center conductive nanomaterial glucose sensor according to claim 1, characterized in that: When R is a monocyclic heterocyclic ligand containing a reactive group, n=1; when R is a bicyclic heterocyclic ligand containing a reactive group, n=0.
3. The bimetallic center conductive nanomaterial glucose sensor according to claim 1, characterized in that: The L is at least one of 2,2′-bipyridine and 4,4′-dimethyl-2,2′-bipyridine; and the R is at least one of bipyridines having an amino group or a carboxyl group.
4. The bimetallic center conductive nanomaterial glucose sensor according to claim 1, characterized in that: The general formula of the silane coupling agent is Y(CH2) n SiX3, wherein n is 0 to 3, X is a hydrolyzable group, and Y is a reactive functional group.
5. The bimetallic center conductive nanomaterial glucose sensor according to claim 4, characterized in that: The X is one or more of methoxy and ethoxy; the Y is one or more of amino and epoxy.
6. The method for preparing the bimetallic center conductive nanomaterial glucose sensor according to any one of claims 1 to 5, characterized in that: The conductive nanomaterial connected with the double metal center redox ligand, glucose oxidase and a crosslinking agent solution are mixed and subjected to a crosslinking reaction at 20 to 45° C. for 45 minutes to 2 days.
Citation Information
Patent Citations
Cationic polymer based wired enzyme formulations for use in analyte sensors
CN102165070A
Analyte sensor apparatuses having interference rejection membranes and methods for making and using them
CN102725629A
Analyte sensors comprising blended membrane compositions and methods for making and using them
CN102762740A
Thermally stable glucose limiting membrane for glucose sensors
CN112088217A
Biocompatible membrane, preparation method thereof and implantable biosensor
CN113521399A